2016
DOI: 10.1001/jamacardio.2016.0529
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Clinical and Functional Outcomes of Atrial Fibrillation in Women and Men

Abstract: clinicaltrials.gov Identifier: NCT01165710.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
149
7
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 195 publications
(183 citation statements)
references
References 24 publications
21
149
7
6
Order By: Relevance
“…Given the higher prevalence of atypical AF symptoms in women, including anxiety, panic, and stress, many providers may not recognize symptomatic AF and instead attribute their patients’ symptoms to other causes . This challenge of diagnosis is further compounded by the described higher frequency of paroxysmal AF in many women, as was seen in our study population, which may result in underdiagnosis of women who are in sinus rhythm at the time of medical evaluation.…”
Section: Discussionmentioning
confidence: 83%
“…Given the higher prevalence of atypical AF symptoms in women, including anxiety, panic, and stress, many providers may not recognize symptomatic AF and instead attribute their patients’ symptoms to other causes . This challenge of diagnosis is further compounded by the described higher frequency of paroxysmal AF in many women, as was seen in our study population, which may result in underdiagnosis of women who are in sinus rhythm at the time of medical evaluation.…”
Section: Discussionmentioning
confidence: 83%
“…Since non-linear relationship between continuous BNP and MACNE and major bleeding was observed (figure 1B,C), continuous BNP was included in the models as a log-transformed continuous variable. Models were adjusted for all covariates listed in the online supplementary eAppendix 2 that were identified by backward selection with a retention criterion of α=0.05 using candidate variables listed in the online supplementary eAppendix 3 as starting covariates in the previous study 19. Importantly, to account for HF status, systolic and diastolic blood pressure, heart rate, New York Heart Association class and left ventricular ejection fraction were included in the models.…”
Section: Methodsmentioning
confidence: 99%
“…Studies exploring patients’ experiences from a gender and age perspective have shown considerable differences between women and men, as well as an impact of age in regard to the effect of arrhythmia on symptoms and HRQoL. There are studies with data from AF‐specific questionnaires, those who have made use of generic and domain‐specific questionnaires and those using a combination of questionnaires . Generic and domain‐specific questionnaires allow for comparisons between patients with different diagnoses while the advantage with a disease‐specific is that it adds specific, disease‐related information …”
Section: Introductionmentioning
confidence: 99%